Blockchains for accelerating open innovation systems for sustainability transitions - Narayan, Rumy; Tidström, Annika (World Scientific Publishing Company, 2019)
Challenges related to climate change, inequality, environmental degradation, and resource scarcity threaten our ability to sustain ourselves while ensuring an equal and prosperous future. The inherent complexity and interconnectedness of these challenges demand a rethinking of our traditional approach towards organizing our production and consumption systems. Transitions towards sustainability require systemic changes, implying a wide network of actors coordinating for new forms of organizing. This chapter proposes that blockchains could offer opportunities for such organizing by leveraging the various combinations of skills, capabilities, and knowledge across open innovation networks to facilitate transitions. The characteristics of open innovation networks and their significance to blockchains are discussed, and their relevance in sustainability transitions. Democratizing access to knowledge and coding trust and consensus through smart contracts make new and innovative economic spaces and opportunities possible. Firms may have to rethink traditional modes of organizing to seize the multiple opportunities that blockchains enabled open innovation systems present.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|